Womenpreneur, Peranan Dan Kendalanya Dalam Kegiatan Dunia Usaha - Tyahya Whisnu Hendratni; Ermalina Ermalina (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
None of the womenpreneurs who later successful because legacy. They all debuted at the top of the business due to sweating, climbing from below. They became rich because of the creative, patient, persistent, and loyal to undergo entrepreneurial process. Number of women entrepreneurs in Indonesia is still minimal namely 0,1% of the total population. The potential for Indonesian women to take part of business sector or business large enough. Moreover, the female population reaches 49% of the total population of Indonesia. The majority of Indonesia women entrepreneurs engaged in levels of Micro Small Medium Enterprises (SMEs), most small moves in the middle to upper level. Although the numbers are still small, women are even more resilient SMEs and proved largely survived the 1998 crisis when the storm hit and 2009.